A Multimodality in Film (The Perspective of Multimodal Discourse Analysis) - M. Bayu Firmansyah; Alfa Julia (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Multimodality involves the strategies employed by semiotic analysis by implicating semiotic modes of interpretation along with technology in media. The object used is the movie Dong Yi (2010). Multimodal discourse in movies is used to express symbols. The symbols in question are the content of messages, sounds, conversations, costumes, movements, images, and so on in the film. The purpose of using multimodal in the film Dong Yi (2010) is to know the form of multimodal discourse in the film and to know the function of multimodal discourse in the film and understand the complexity of meaning that needs to be analyzed multimodally. The aspects of multimodal discourse used in Dong Yi (2010) Episode 5 are language, image, music, sound, and movement by optimizing the realization of semiotics. This research uses multimodal discourse approach with qualitative research type. The results found 12 language data, 30 image data, 14 music data, 19 sound data, 8 movement data. Dong Yi (2010) episode 5 optimizes five aspects of multimodality (language, image, music, sound, and movement) by using ideas from other eras and as a potential meaning of the experience of ideas in the discourse process. The function of multimodal discourse in the movie Dong Yi (2010) Episode 5 is to complement and strengthen previous research in the field.